Nilai yang Dirasakan Dari Produk Sepatu dan Niat Pembelian Kembali Konsumen - Aisyah, Rika Isti; Suhaeni, Tintin (Jurnal Riset Bisnis dan Investasi, 2019)
Abstract: The concept of perceived value has become a key to gain a competitive advantage to retain consumer in long term. The purpose of this study is to identify how much influence given by perceived value to repurchase intention of shoe product to consumer of PT Ganesha Brodo Indonesia in Bandung. This research was conducted on 100 respondents with purposive sampling technique and analyzed using descriptive method. From result of research shows that Brodo delivering superior consumer value that can enables a firm to achieve favorably repurchase intentions equal to 47,3%. Keywords: consumer, perceived value, repurchase intention